Membrane complement regulatory protein reduces the damage of transplanting autologous bone marrow mesenchymal stem cells by suppressing the activation of complement. Issue 10 (October 2017) - Xiao, Kai; Fang, Zhenhua; Gao, Xinfeng; Zhao, Jingjing; Huang, Ruokun; Xie, Ming
Abstract: There are few studies on the interaction of transplanting autologous bone marrow mesenchymal stem cells (BMSCs) and complement. In order to further explore the effect of complement on BMSCs, BMSCs were obtained from bone marrow of 20 cases clinical patients, and then experimented in vitro. The cytotoxicity of complement on the mesenchymal stem cells in autologous human serum (AHS) was measured by Europium cytotoxicity assay. The complement membrane attack complex (MAC) deposited on the membrane surface was detected by flow cytometry. Finally, the cytotoxicity on BMSCs was measured after mCRPs overexpression or knockdown. We found that more than 90% of cells derived from bone marrow were identified to be mesenchymal stem cells through detection of cell membrane surface markers by flow cytometry. BMSCs harvested from the 20 patients all had cytotoxicity after incubated with AHS, and the cytotoxicity was significant higher than that incubated with complement inactivated autologous human serum (iAHS). Complement attack complex (MAC) could be detected on the BMSCs incubated with AHS, which implied the complement activation. We also found that mCRPs CD55 and CD59 overexpressions can resist the cytotoxicity induced by complement activation, while mCRPs CD55 and CD59 knockdown can enhance the cytotoxicity. Thus, the results indicated that mCRPs could effectively protect BMSCs from attacking by complement by suppressing the activation of complement.